OPTIMIZATION OF THE CONDITIONS OF MACHINING PARAMETERS BASED ON A CRITERION COMBINED BY GENETIC ALGORITHMS - Djari, D.; Manaa, R.; Bensaada, S. (Science des matériaux (Laboratoire LARHYSS); Vol. 1 (2014): Science des matériaux, 2014)
In metal cutting processes, cutting conditions have an influence on reducing the production cost and time and deciding the quality of a final product. This paper deals with the multiple- objective optimization of machining conditions problem in order to optimize the time and production cost simultaneously. This method consists essentially of improving previous methods by introducing the Pareto technique for solving the multiple-objective optimization problem using Genetic Algorithm. This method has been used for single pass turning. A comparison between results obtained by the proposed approach and those obtained with the gradient and the simplex methods was carried out.